GAGASAN PLURALISME AGAMA GUS DUR UNTUK KESETARAAN DAN KERUKUNAN - Surya Adi Sahfutra (Religi: Jurnal Studi Agama-agama, 2014)
This article focuses on framing the thought of  Abdurrahman Wahid on reli- gious pluralism. Gus Dur-his familiar name, is a figure of the Muslim scholars, clerics, and also a politician who has a considerable influence in the national life in Indonesia. The idea of religious pluralism was offered by Gus Dur calls for recognition of the equal right to claim the truth of any religion by its followers, respectively. For Gus Dur difference faith/theology should not affect the enforce- ment of  justice. Ever y religion should receive equal treatment before the law; hence neither group feels superior to the other.The author argues that the research on the views of  Gus Dur is ver y important to see what is meant by religious pluralism. From this study we can also see the mapping of  what Gus Dur strug gled in upholding religious pluralism. By using critical-thinking approach, Gus Dur’s tought will be dissected to obtain a com- prehensive understanding of  the globalizing thought of  Gus Dur which covering various aspects of life, not only limited in political issues, the relationship be- tween religion and the state as well as inter-religious relations. The result can be described that there are three focuses of  Wahid fought in the religious pluralism, namely equality of religions, tolerance and interfaith and inter-religious dialog.